2013
DOI: 10.1002/fuce.201200127
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Verification of the Polymer Electrolyte Fuel Cell Performances Enhanced by Under‐Rib Convection

Abstract: Understanding the current density distributions in polymer electrolyte fuel cells (PEFCs) is crucial for designing cell components, such as the flow field of bipolar plates. A new serpentine flow field equipped with sub‐channels and by‐passes (SFFSB) was numerically and experimentally confirmed to enhance the reactant transport rates and liquid removal efficiency compared with a conventional advanced serpentine flow field (CASFF). Consequently, the maximum current and the power densities of the SFFSB were incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The fuel cell operation is characterized as gas transport and transformation of one species to another [25]. The geometric details and other physical parameters of the cell components used in this research can be found in our previous papers [1,[26][27][28] and are summarized in Tables 1-3. Table 2.…”
Section: Simulation Model Description and Computational Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…The fuel cell operation is characterized as gas transport and transformation of one species to another [25]. The geometric details and other physical parameters of the cell components used in this research can be found in our previous papers [1,[26][27][28] and are summarized in Tables 1-3. Table 2.…”
Section: Simulation Model Description and Computational Domainmentioning
confidence: 99%
“…Table 2. Geometric details of the cell components used in this simulation [1,[26][27][28]. GDL: gas diffusion layer.…”
Section: Simulation Model Description and Computational Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…One direction is to develop the under-rib mass transport. The roles of the under-rib mass transport were previously studied [2,[12][13][14][15][16][17][18][19][20][21][22]. It was reported that for a specified mass flow rate, the under rib convection is mainly affected by different factors such as the rib width, the pressure difference between the adjacent channels, and the diffusion layer permeability [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers investigated the serpentine flow field with adding sub-channel and bypasses between the conventional channels to control the under-rib convection. They concluded that these additions enhance the reactant transport, enable more effective utilization of the electrocatalysts, and improve the reaction products removal [12,13,18,22].…”
Section: Introductionmentioning
confidence: 99%